Nutritional impact of highly pathogenic avian influenza in Kenya - Iannotti, Lora L.; Roy, Devesh (SAGE Publications, 2013)
Outbreaks of highly pathogenic avian influenza (HPAI) (virus type H5N1) have led to extensive bird culling and other control measures throughout the world, with implications especially for the livelihoods of the poor. There is limited empirical evidence for the impact of HPAI on poultry consumption and nutrition of vulnerable populations.To test the effect of reduced per capita poultry consumption at the household level due to an HPAI event on anthropometric measurements of children.This study used data from the Kenya Integrated Household Budget Survey (KIHBS) 2004/05 to characterize the nutritional status of young children 6 to 36 months of age, household dietary diversity (number of food groups consumed), and determinants of anthropometric outcomes, including z-scores for height-for-age (HAZ), weight-for-age (WAZ), and weight-for-height (WHZ). Propensity score matching (PSM) was applied to ascertain the nutritional impacts of reduced poultry consumption arising from an HPAI event.Thirty-four percent of the children were stunted (HAZ < −2 SD), 16% were underweight (WAZ < −2 SD), and 8% were wasted (WHZ < −2 SD), with the highest prevalences in the Coast, Eastern, North Eastern, Nyanza, and Rift Valley provinces. On average, households reported consuming food from 2.5 ± 1.3 food groups per week. Consistently significant determinants of anthropometric outcomes in these children were child's age, child's sex, household level of education, and various income and wealth determinants. PSM demonstrated that a reduction of consumption of poultry meat and eggs due to HPAI infection would increase the prevalence of stunting by 3.9 percentage points (Average Treatment Effect on the Treated (ATT), p = .06), increase the prevalence of underweight by 5 percentage points, and reduce WAZ by 0.16 (ATT, p = .03).Through the household dietary diversity and consumption pathways, HPAI could have nutrition-related consequences with public health significance. In the event of HPAI, action may be needed to protect the nutrition of young children 6 to 36 months of age.